DAMPAK KEBERADAAN PMKS PT. INTI INDOSAWIT SUBUR TERHADAP SOSIAL EKONOMI MASYARAKAT DESA MEKAR JAYA KECAMATAN PANGKALAN KERINCI KABUPATEN PELALAWAN - Roma Br Sitorus; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study aims to determine the impact of the PMKS PT. Inti Indosawit Subur towards the socio-economic conditions of the community of Desa Mekar Jaya. This research design is in the form of descriptive quantitative with sample selection using a simple random technique. The data collection tools used was questionnaire sheets, documentation, and direct observation. The total population in the study was 700 people who live in Desa Mekar Jaya with a sample size of 100 respondents who were obtained using the Slovin formula, with a 10% leeway percentage used. The results of this study indicate that the impact of PMKS is examined from 2 aspects, namely the impact of PMKS on social conditions and the impact of PMKS on economic conditions. The positive impact of PMKS on social conditions is in the high (10.0%), medium (18.0%) and low (22.0%) categories while the negative impacts of PMKS on social conditions are in the high category (10.0%), the medium category (19.0%) and the low category (21,%). The positive impact of PMKS on economic conditions was in the medium category (24.0%) and the low category (26.0%) while the negative impact of PMKS on economic conditions are in the high category (8.0%), the medium category (32.0%) and the low category (10.0%). Based on the results of this study, it was suggested to PMKS PT. Inti Indosawit Subur to pay more attention to factory activities that affect the social and economic conditions of the Desa Mekar Jaya Community. Keywords        : Impact, Socio-economic, Community